Case report: Page kidney with multiple serosal effusions caused by bilateral spontaneous renal subcapsular hemorrhage - Wang, Leibo; Qiu, Zuze; Zhan, Shun; Shi, Guanyu; He, Wei; Cen, Zhuangding; Xu, Feng; Tian, Wu; Li, Daobing (Frontiers in Medicine, 2024)
pressing on the renal parenchyma and is a rare cause of secondary hypertension. In this paper, we report a case of Page caused by bilateral spontaneous subcapsular renal hematoma, the main manifestations of which were secondary hypertension, multiple serous effusion, and renal insufficiency. After admission, drug blood pressure control was ineffective. After bilateral perirenal effusion puncture and drainage was performed to relieve bilateral perirenal compression, Blood pressure gradually dropped to normal, multi-serous cavity effusion (pericardial, thoracic, and abdominal effusion) gradually disappeared, and kidney function returned to normal. Secondary hypertension caused by Page kidney can be treated. When Page kidney is complicated with multiple serous effusion, the effect of antihypertensive drugs alone is poor, and early perineal puncture drainage can achieve better clinical efficacy.